Transformation of Ukraine’s Maritime Legislation: Impact Factors, Regulatory Methods, and Future Outlooks - Фасій, Богдан Володимирович; Фасій, Б. В.; Fasii, Bohdan V. (Odesa : Publishing House Helvetica, 2025)
The article examines recent changes in Ukraine’s maritime and seaport regulatory environment amidst significant political, economic, and security pressures. The research explores the drivers of legislative change, including military aggression, European integration commitments, civil law reforms, and the expansion of digital governance tools. Attention is given to how regulatory methods and techniques are adjusted through strategic policy instruments, the interaction between public and private law mechanisms, the implications of abolishing the Commercial Code of Ukraine, the increasing influence of international standards and soft-law instruments, and wartime regulatory innovations. The analysis indicates that Ukraine’s maritime legislation is shifting toward a hybrid regulatory model that combines binding public regulation with flexible private-law arrangements and programmatic state intervention. This approach strengthens institutional resilience, maintains maritime trade continuity, and allows for legal adaptation in conditions of prolonged instability. The article concludes that Ukraine’s experience adds to a broader understanding of adaptive maritime regulation in states facing systemic disruption.
Fasii B. Transformation of Ukraine’s Maritime Legislation: Impact Factors, Regulatory Methods, and Future Outlooks / B. Fasii // Lex Portus. – Odesa : Publishing House Helvetica, 2025. – 11(6). – P. 21–32. Режим доступу: https://hdl.handle.net/11300/32434
Keywords: maritime legislation; seaport governance; legal regulatory methods; public and private law interaction; wartime regulation; civil law recodification; international maritime standards; digitalization